Proceedings of the 34th ACM/SIGAPP Symposium on Applied Computing 2019
DOI: 10.1145/3297280.3297472
|View full text |Cite
|
Sign up to set email alerts
|

The ROP needle

Abstract: In recent years, researchers have come up with proof of concepts of seemingly benign applications such as InstaStock and Jekyll that remain dormant until triggered by an attacker-crafted condition, which activates a malicious behavior, eluding code review and signing mechanisms. In this paper, we make a step forward by describing a stealthy injection vector design approach based on Return Oriented Programming (ROP) code reuse that provides two main novel features: 1) the ability to defer the specification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 30 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Ntantogian et al [21] proposed using code-reuse methods to hide malicious functionality from detecting by antivirus tools, while Mu et al [22] suggested using ROP to obfuscate the code. Code-reuse methods allow for backdoors to be inserted into software [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Ntantogian et al [21] proposed using code-reuse methods to hide malicious functionality from detecting by antivirus tools, while Mu et al [22] suggested using ROP to obfuscate the code. Code-reuse methods allow for backdoors to be inserted into software [23,24].…”
Section: Introductionmentioning
confidence: 99%